ANAK CEREBRAL PALSY N SANG JUARA DESAIN KOMUNIKASI VISUAL - Al- Rumby (Jurnal Penelitian Pendidikan Khusus, 2014)
ABSTRAK The background of this study was the presence of cerebral palsy children with the initials N school at SMK Negeri 4 Padang. Children have distractions and obstacles in body function that is the stiffness in the hands and the movement can not be controlled without children. With all the shortcomings that are owned by the child, N cerebral palsy, he was still able to carve a remarkable achievement in the academic and non-academic, namely in the field of visual communication design. But the achievements are still many obstacles that he faced in the absence of which a special assistant teachers (GPK) and there is no means of helping children to attend classes and practice with the condition of his son having trouble to write notes and take exams. So that the constraints experienced by the child, then the efforts of schools that provide laptops means to help the child to take the test and the teacher gave the theory of special treatment such as extra time to complete the task to ank and training.   Kata Kunci: Anak Cerebral Palsy; Cara Belajar; Prestasi